On the Perception of Time in Ancient Greece - Harry, Chelsea C (In Anderen Zeiten/In Other Times: Zeitdiskurse im Wandel/ Changing Discourses of Time across Human History, 2022)
Keywords: dept.phi

Introduction: Schelling and the Environment - Harry, Chelsea C. (Environment, Space, Place, 2022)
Keywords: dept.phi

Why Controlling the Historical Narrative Matters: A Jamesian Response - Marsoobian, A.T. (Pragmatism Today, 2022)
An examination of the lessons learned from William James’s oration on the dedication of the Civil War Monument memorialization Colonel Robert Shaw and the Fifty-Fourth Regiment Massachusetts Infantry, an all-Black unit. The role of monuments in making visible the values of a society is explored in the context of promoting a nation’s historical narrative, in particular in their propagation of the South’s Lost Cause narrative. The genocidal violence against Armenians in the Caucasus by the Azerbaijani regime serves as the second illustration of the abuse of historical narratives. © 2022 Central European Pragmatist Forum. All rights reserved.
Keywords: Armenians; Azerbaijan; Civil War monuments; William James; civic courage; dept.phi; genocidal violence; historical narratives; peer-reviewed; the Lost Cause; ⛔ No DOI found